2021
DOI: 10.21037/tcr-20-3421
|View full text |Cite
|
Sign up to set email alerts
|

The predictive and prognostic value of sex in localized colorectal cancer: a SEER-based analysis

Abstract: Background: Although the influence of sex on different cancer survival has been investigated, the predictive and prognostic value of sex in localized colorectal cancer (CRC) still remain controversial.Methods: Survival was evaluated in patients who diagnosed with localized CRC in the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and 2016. Overall survival (OS) outcomes were estimated with the Kaplan-Meier method, and multivariable Cox regression was used to calculate hazard ratios (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…While some studies have found that age and sex have little or no bearing on the risk of death in patients with colorectal cancer [ 43 ], the present study outcome shows gender to be a significant predictor of death (survival) as the male gender has about a three-fold increased risk of dying from colorectal cancer in an at-risk range of 2–9 times (95% CI) than the female patients ( p -value = 0.040). Similar findings have also been reported in several studies [ 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…While some studies have found that age and sex have little or no bearing on the risk of death in patients with colorectal cancer [ 43 ], the present study outcome shows gender to be a significant predictor of death (survival) as the male gender has about a three-fold increased risk of dying from colorectal cancer in an at-risk range of 2–9 times (95% CI) than the female patients ( p -value = 0.040). Similar findings have also been reported in several studies [ 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…Numerous epidemiological studies have linked a lower risk and higher survival rate to increased estrogen exposure in adult females [ 24 , 25 ]. Selecting age 60 as the cutoff point ensures that patients older than 60 years are postmenopausal [ 8 ], further highlighting the significance of hormone levels in both sexes. Additionally, various other factors, including epigenetic and genetic factors, sex hormones, and psychosocial aspects, contribute to the observed differences.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that sex is one of the key factors influencing cancer survival and prognosis, including colon [ 8 ], stomach [ 9 ], and esophageal cancers [ 10 ]. Research has shown that the majority of HCC patients are male, with a male-to-female ratio ranging between 1.5 and 4.0 [ 11 , 12 ], indicating that sex may also be a crucial factor influencing the prognosis of HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer diagnosed globally 1 and represents 9% of all new cancer cases in the United States. 2 Whereas patients with localized disease have a high survival rate, metastatic CRC is lethal with a 5 year survival of ∼13%. 3 Genomic characterization combined with immunohistochemistry analysis of tumors remains the standard practice to guide initial treatment choices.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer diagnosed globally and represents 9% of all new cancer cases in the United States . Whereas patients with localized disease have a high survival rate, metastatic CRC is lethal with a 5 year survival of ∼13% .…”
Section: Introductionmentioning
confidence: 99%